A decision support tool for parasite management in fish aquaculture. (7th March 2022) - Hutson, Kate Suzanne; Mooney, Allan James; Ernst, Ingo; Brazenor, Alexander Karlis; Scheel, Max; Atalah, Javier
Abstract: A decision support tool was developed to aid management of problematic parasites in marine fish aquaculture. The tool provides biologically relevant treatment intervals to interrupt the life cycle of ectoparasitic flatworms that occur in global kingfish and amberjack ( Seriola spp.) aquaculture. Temperature‐dependent life cycle parameters for the 'skin flukes', Benedenia seriolae and Neobenedenia girellae, and the 'gill fluke', Zeuxapta seriolae, were derived from published data and modelled using non‐linear regressions. Increasing temperatures shortened the duration of most life cycle parameters of all parasites. Salinity had no effect on the timing of life cycle parameters but limited hatching success in hypo‐ and hypersaline conditions. The tool, named BeNeZe after the first two letters of each parasite genera, enables rapid determination of treatment intervals for two consecutive medicinal immersion or 'bathing' treatments—the first to kill adult flatworms attached to fish and the second to prevent maturity of new parasite recruits. As temperature increases, the interval between treatments and the 'window' within which the second treatment should be applied is reduced. The tool can be used for multi‐species infections. The inclusion of parasite taxonomy, biology and behaviour as part of an integrated management strategy is reviewed. Available through an open access app, BeNeZe is intended to be applied in conjunction with farm biosecurity, surveillance, management measures and recognition of independent management units. BeNeZe can be used to reduce infection burdens, improve fish welfare and production and reduce treatment number and frequency.